Advances in Nutrition Science and Integrative Physiology: Insights From Controlled Feeding Studies - Davy, Kevin P.; Davy, Brenda M. (Frontiers in Physiology, 2019)
Nutrition science is a highly impactful but contentious area of biomedical science. Establishing cause and effect relationships between the nutrients and/or diets we consume and the avoidance of or risk of disease is extremely challenging. As such, evidence-based nutrition is best served by considering the totality of evidence across multiple study types including nutritional epidemiological studies, randomized controlled trials of behavioral interventions, and controlled feeding studies. The purpose of the present review is to provide an overview for those conducting research outside of clinical nutrition on how controlled feeding studies can be used to gain insight into integrative physiology/metabolism as well as to inform dietary guidelines. We discuss the rationale, basic elements, and complexities of conducting controlled feeding studies and provide examples of contributions of controlled feeding studies to advances in nutrition science and integrative physiology. Our goal is to provide a resource for those wishing to leverage the experimental advantage provided by controlled feeding studies in their own research programs.